Feed-Back Loop: From Perception to Brain-Time - RODRIGUES, Nuno (2014)
Critical Studies: Art, Becoming and Participation marks the launch of the Visual Arts and Critical Studies Group, recently formed within the scope of the Arnaldo Araújo Research Centre (CEAA). The book seeks to rehearse what may become, in the next future, a Brute Theory, whose territories of action remain under definition but whose company we wish to keep along future trajectories. As the singular is a collective, in this publication dispersion overrides the search for any type of unity. Brute Theory, as a pocket of resistance to current models of academic domination anchored in profitable, efficient and, as repeatedly stated, competitive research, proposes precarious dynamics, such as risk and drift.